1990
DOI: 10.1093/oxfordjournals.aje.a115738
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Case-Control Study of the Correlates of Early Menarche

Abstract: Age at menarche, an early determinant of breast cancer risk, shows both a downward secular trend and marked differences by socioeconomic status, both presumably the reflection of dietary variations. A cohort study is being conducted in the Quebec City, Canada, area to assess the relation between diet, physical activities, and menarche. In the fall of 1986, 3,022 fifth-grade girls (mean age, 10.7 years) agreed to participate in the study. All of the girls' parents provided information on health, familial, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
95
5
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 0 publications
10
95
5
1
Order By: Relevance
“…A possible mechanism is that early maturing adolescents (girls) appear to have increased blood concentrations of estrogen hormone at an earlier age. 41 It has been found that a high circulating level of estrogen persists until the age of 25 years and leads to the accumulation of adipose tissues in the body 42 or that a longer period of positive energy balance in early maturers leads to increased obesity. 23 However, because our study indicated higher BMI related to pubertal maturity in both boys and girls, this may explain only a part of the association between puberty and adult obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism is that early maturing adolescents (girls) appear to have increased blood concentrations of estrogen hormone at an earlier age. 41 It has been found that a high circulating level of estrogen persists until the age of 25 years and leads to the accumulation of adipose tissues in the body 42 or that a longer period of positive energy balance in early maturers leads to increased obesity. 23 However, because our study indicated higher BMI related to pubertal maturity in both boys and girls, this may explain only a part of the association between puberty and adult obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the factors known to affect menarcheal timing, genetics via maternal tempo is the most obvious; menarche is early in girls whose mothers had an early menarche (Moisan et al 1990). Yet as already discussed this factor does not explain the secular trend; the gene pool has not had sufficient time to respond.…”
Section: Menarcheal Factorsmentioning
confidence: 99%
“…Nutrition during infancy is directly associated with weight gain, which also has a dominant effect on the development of puberty. Although breast-feeding has been recommended to prevent early puberty, there are conflicting opinions regarding whether breast-feeding is related to a decrease in age of puberty onset (8)(9)(10)(11) . Recently, a study reported that an additional month of breast-feeding decreases the risk of earlier menarche (5) , but that study did not consider postnatal growth.…”
mentioning
confidence: 99%